Cotton wastes for composite reinforcement / Mohd Iqbal Misnon - Misnon, Mohd Iqbal (2007)
This study assesses the possibility of fabricating composites out of cotton waste. Two (2) types of cotton wastes were taken from a spinning mill and used in this study , which were blowing waste and comb noils. Two (2) types of matrices were used in this project: polyester resin (thermosets) and polypropylene (thermoplastic). Composite materials were fabricated using compression with mould (hot press) for thermoplastic resin and compression without mould for thermoset resin. Tensile and flexural test were done in order to assess the mechanical properties of cotton waste composites. Statistical analysis using ANOVA (analysis of variance) and post hoc; Duncan were derived to test any significant difference in tensile and flexural strength results. Comb noils-polyester composite was found to produce the highest result in tensile and flexural strength which are 71.01 MPa and 126.85 MPa respectively. The lowest is exhibited by blowing waste-polyester composite which is 48.73 MPa and 83.63 MPa for tensile and flexural strength. Comb noils-polypropylene composite also show the highest tensile and flexural strength of 54.22 MPa and 75.60 MPa respectively and the lowest is exhibited by comb noils-polypropylene composite via crushing method which are 26.97 MPa for tensile and 58.75 MPa for flexural strength. Regression and correlation analysis was also done in order to determine the trend of all the parameters. Good relationship between tensile and flexural properties was also found with cotton waste composites. It was also found that a positive correlation existed for tensile and flexural prop~rties with the length of the waste fibres used . The longer the length of the fibres , the higher would be the strength. However , this is only true for normal size textile fibres and not the nano and other smaller size fibres.